Employee Ownership: Revolution or Ripoff?Employee Ownership: Revolution or Ripoff? by BlasiJoseph R.. Cambridge, MA: Ballinger, 1988, $27.95, cloth. - Hammer, Tove Helland (Academy of Management Review, 1989)
The article reviews the book “Employee Ownership: Revolution or Ripoff'” by Joseph R. Blasi.